A Case Study Of Mexter Technology Berhad - Anthony, Vera Kalaivani (2008)
Mexter technology Berhad was one of the company that took advantage of the MSC development. The Mexter Group is a diversified technology company with the vision and foresight to move into the fast-growing ICT sector more than a decade ago.